Hubungan Kualitas Puasa dan Kebahagiaan Santri Pondok Pesantren Al-Ihsan - Pipih Muhopilah; Witrin Gamayanti; Elisa Kurniadewi (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2018)
Fasting is one of worship rituals that is usually done by santri, but they have many activities in boarding school and campus that caused not only positive but also various negative effects. These effects may lower the productivity and life satisfaction, and increase negative emotion. This research aims to examine the relationship of fasting quality and happiness. This study used quantitative method with the fasting quality scale based on Al-Ghazali’s theory and Oxford Happiness Questionnaire, which is analyzed by Pearson analysis method. Total respondent for this research is 150 respondents. The result of this research shows that the quality of fasting had correlation with santri’s happiness, with percentage is 0.466. When fasting santri avoided to do something bad, be more patient, and tried to do anything according with guidance from Allah that it causes positive emotion and satisfaction, so they have high quality of fasting and happiness.